Model Kinerja Keuangan untuk Peningkatan Nilai Perusahaan pada Sektor Perusahaan Makanan dan Minuman di Bursa Efek Indonesia - Tasya Sekar Putri; Muhammad Fachrudin Arrozi (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of Activity Ratio, Profitability, and Liquidity on Price to Book Value, either simultaneously or partially. In this study, the dependent variable of firm value was measured using Price to Book Value (PBV). The object of this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method used is purposive sampling. The sampling technique was 14 companies with a research period of 2017-2021. The type of data used in this study was secondary data. This research uses Multiple Linear Analysis method. The results of the study show that the Activity Ratio, Profitability, and Liquidity have a significant effect on Firm Value. Activity and Liquidity Ratios have no partial effect on Firm Value. Meanwhile, profitability has an effect on firm value partially.